A change in the study evaluation paradigm reveals that larynx preservation compromises survival in T4 laryngeal cancer patients - Dyckhoff, Gerhard; Plinkert, Peter K.; Ramroth, Heribert (BMC cancer, 2017)
Larynx preservation (LP) is recommended for up to low-volume T4 laryngeal cancer as an evidence-based treatment option that does not compromise survival. However, a reevaluation of the current literature raises questions regarding whether there is indeed reliable evidence to support larynx preservation for T4 tumor patients.